What Governs Immediate or Delayed Cardioversion of Atrial Fibrillation by Direct Current Shock? - Amar T. AL-Hamdi; Azad J. Ali; Becker S. Alzand (مجلة كلية الطب)
Background: Aftershock delivery and direct current DC-cardioversion of atrial fibrillation may be immediate or delayed.